2017
DOI: 10.1016/j.celrep.2017.08.096
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Activated Adipose Tissue Macrophages Perform Detrimental and Beneficial Functions during Diet-Induced Obesity

Abstract: SUMMARY During obesity, adipose tissue macrophages (ATMs) adopt a ‘metabolically-activated’ (MMe) phenotype. However, the functions of MMe macrophages are poorly understood. Here we combine proteomic and functional methods to demonstrate that in addition to potentiating inflammation, MMe macrophages also promote dead adipocyte clearance through lysosomal exocytosis. We identify NADPH-oxidase-2 (NOX2) as a driver of the inflammatory and adipocyte-clearing properties of MMe macrophages, and show that compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
213
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(236 citation statements)
references
References 42 publications
6
213
0
3
Order By: Relevance
“…The role of NOX2‐dependent ROS in modulating the severity of obesity‐associated glucose dysmetabolism is controversial . Hence, the development of glucose dysmetabolism and insulin resistance was examined.…”
Section: Resultsmentioning
confidence: 89%
“…The role of NOX2‐dependent ROS in modulating the severity of obesity‐associated glucose dysmetabolism is controversial . Hence, the development of glucose dysmetabolism and insulin resistance was examined.…”
Section: Resultsmentioning
confidence: 89%
“…1). [17][18][19] Evidence has suggested that obesity-associated ATMs include highly plastic cell populations, whose immuno-phenotype is determined in response to multiple stimuli in their surrounding microenvironment. [17][18][19] Evidence has suggested that obesity-associated ATMs include highly plastic cell populations, whose immuno-phenotype is determined in response to multiple stimuli in their surrounding microenvironment.…”
Section: Atm Activation Statesmentioning
confidence: 99%
“…It is now evident that more than one population of ATMs exist in obese AT, 20 and these distinct populations express specific markers, have unique tissue distributions, transcriptional profiles and functions. 19 Obese ATMs display surface markers that resemble neither classical (M1) nor alternative (M2) activation, but rather a state of metabolic activation (MMe) induced by diverse metabolic stimuli (e.g. In obesity, ATMs adopt a metabolic activation state with prominent lysosomal activity, 17,18 with the main purpose to clear dead adipocytes.…”
Section: Atm Activation Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity leads to exacerbated leptin release by the adipose tissue. In obese mice, saturated free fatty acids (FFAs) produce a pro‐inflammatory Mϕ phenotype that is mechanistically distinct from M1 or M2 activation . During differentiation of monocytes into Mϕs, Ob‐Rb is up‐regulated and maintained after differentiation, providing stronger responses to leptin by Mϕs .…”
Section: Leptin and Mϕ Immunoregulationmentioning
confidence: 99%